Hak untuk Kesehatan dalam Konteks Medical Tourism Berdasarkan Perspektif Hak Asasi Manusia - Dwi Lestari Indah Sari (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
Medical tourism is a global phenomenon in which individuals travel across countries to receive medical or health care. Although not directly recognized as a major component of human rights (HAM), medical tourism has a relevant impact on human rights aspects in countries like Indonesia. The Indonesian government has an important role in regulating medical tourism by taking into account the human rights framework. This involves developing regulations that ensure the protection of patient rights, monitoring quality medical practice, and fulfilling access to health services for all citizens, both local and medical tourists. This article provides a brief analysis of how medical tourism can impact several aspects of human rights including the right to health. However, this approach also raises questions about equitable access to medical care for local populations. In order to maintain a balance between benefits and negative impacts, implementing medical tourism in accordance with human rights principles will support the sustainable goal of providing quality and equitable medical care for all individuals, without violating human rights.